62 Galectin-3 as a marker of unstable coronary plaque. (5th October 2017) - Bajrangee, A; Arkins, L; Brennan, M; Cox, D; Maree, AO
Abstract : Introduction: Galectin-3 (Gal-3) is a pleiotropic lectin that is upregulated when monocytes differentiate into macrophages. It plays an important role in cell proliferation, angiogenesis and apoptosis. We aimed to determine the utility of Gal-3 as a marker of coronary plaque rupture and unstable plaque. Methods: Consecutive patients presenting with chest pain to the emergency department of St James's Hospital, Dublin and those referred directly for angiography were enrolled between September 2014 to December 2015. Patients were divided into non-cardiac chest pain (NCCP), stable angina (SA) and acute coronary syndrome (ACS-unstable angina, NSTEMI and STEMI) based on clinical presentation, chest pain scoring tools (HEART, TIMI and GRACE score), electrocardiogram changes, troponin measurements and angiographic data. GENSINI and Syntax scores were used as measures of total plaque burden at angiography. Serum concentration of Gal-3 (0.3–10 ng/ml) was performed by ELISA ( R and D Systems Inc) . Results: Patients (n=191), with NCCP (n=96), with SA (n=47) and with ACS (n=48) were enrolled. Mean age was 61± 11 years with 65% males. The mean concentration of Gal-3 in NCCP was 8.4± 0.3 ng/ml, 9 ± 2.3 ng/ml in SA and 9.8 ± 2.6 ng/ml in ACS (p =0.02). In patients with symptoms of chest pain within the preceding 12 hours (NCCP=50, SA= 27, ACS= 42) the mean concentration of Gal-3 was 10.1± 0.4 ng/ml for ACS, 9.1± 1.7 ng/ml in SA and 8.7± 0.3 ng/ml in NCCP (p = 0.01). In patients with UA who were troponin negative and less likely to have undergone plaque rupture, Gal-3 was significantly elevated compared to both NCCP and SA at 10± 1.8 ng/ml (p<0.001). Table 1 highlights the correlations between Gal-3 and ACS patients. Conclusion: Gal-3 was significantly elevated in ACS patients with plaque instability and rupture. In UA patients who were troponin negative and less likely to have undergone plaque rupture Gal-3 was significantly elevated. Gal-3 may be a marker of unstable coronary plaque where myocardial infarction has not occurred.